Kualitas Layanan Terhadap Kepuasan Pengguna Jasa Commuter Line Parung Panjang - Nurmalasari - Nurmalasari; Adhitya Dinhar (Universitas Bina Sarana Informatika, 2018)
Improving the quality of service to consumers is a major priority in companies engaged in public transportation. The purpose of this research is to analyze and know the level of commuter line user satisfaction that they feel. The type of research used is descriptive quantitative. For data collection includes literature study and field study by way of observation and distribution of questionnaires. This collection sample was collected from 100 respondents residing in Bekasi station. Based on the results of questionnaire analysis with multiple regression method, it can be concluded that there are seven factors that must be improved because not satisfactory, which include: seating capacity, cleanliness, functioning of train facilities, available tools to provide travel route info, accuracy of departure schedule, and willingness of officers to appreciate and prioritize the needs of Commuter Line users. While some factors according to the respondents are important and satisfactory, are: the speed and accuracy of the officer in providing services, the ability to provide the best service, as evidenced by the dimensions of service quality that exist only dimensions of assurance variables that have a significant level 0.36 <0.05 and tangible variables has a significant level of 0.000 <0.05 most influential in the face of commuter line user satisfaction.